Deteksi Objek Nomor Kendaraan Pada Citra Kendaraan Bermotor - Komariyuli Anwariyah (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
Motor vehicle police numbers recognation is one of the most important topics in the processof building a smart transportation system. Also this concept and introduction system will bevery useful in various combinations of applications, including in monitoring vehicles when acrime occurs. In this research an object recognition model will be developed by reviewing thesize of the object vertically. Image processing stages starting from the stages of image sizechange, image grayscale, edge detection, morphological operations to the segmentation stage.Based on tests conducted, it was found that the implemented model can be used in the processof recognizing vehicle numbers in the image of motorized vehicles